Dekonstruksi Makna Kuasa dalam Matriarchy - Chuzaifah, Yuniyanti (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2002)
This article an anthropological work by Peggy Reeves Sanday, who, between 1981 and 1999 traveled many times to West Sumatera, particularly to the Belubus area. This book attempts to answer the often-asked question as to whether Minang constitutes a genuine matriarchy, not just a form of matrilineal ties? This question arises from the fact that many thing are considered to have changed in the Minang social system, where power is in the hands of men in areas such as control of the state system, where authority in policy-making is male dominated, and where land ownership was brought under a policy of agrarian certification, where certificates were given to the head of the family, which by definition was male. The dominant discourse that bas developed can be said to judge that the Minangkabau of course adhere to the matrilineal tradition, but in reality are highly patriarchal. However, in this book, Peggy tries to overturn this view.DOI: 10.15408/sdi.v9i2.670